2023
DOI: 10.1257/jel.20211658
|View full text |Cite
|
Sign up to set email alerts
|

Designing Information Provision Experiments

Abstract: Information provision experiments allow researchers to test economic theories and answer policy-relevant questions by varying the information set available to respondents. We survey the emerging literature using information provision experiments in economics and discuss applications in macroeconomics, finance, political economy, public economics, labor economics, and health economics. We also discuss design considerations and provide best-practice recommendations on how to (i) measure beliefs; (ii) design the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(101 citation statements)
references
References 249 publications
0
57
1
Order By: Relevance
“…We see the potential to include personality traits in behavioral economic experiments, for instance, checking whether custom-tailoring decision settings around farmers' personalities can be effective. This seems especially promising against the background of the increasing interest of economists in information provision experiments (Haaland et al, 2023). Thirdly, there is some potential to improve the data quality, when focusing on farmers' Big Five.…”
Section: Discussionmentioning
confidence: 99%
“…We see the potential to include personality traits in behavioral economic experiments, for instance, checking whether custom-tailoring decision settings around farmers' personalities can be effective. This seems especially promising against the background of the increasing interest of economists in information provision experiments (Haaland et al, 2023). Thirdly, there is some potential to improve the data quality, when focusing on farmers' Big Five.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, these causal estimates help clarify how cultural or partisan gaps in attitudes, behavior, and policy preferences may emerge as a result of information exposure. Our analysis of partisanship and the news diet distinguishes our paper from many information experiments in the literature, many of which are reviewed by Haaland et al ( 20 ). In relevant work, Faia et al ( 21 ) studies how partisan views interact with information selection and processing, leading media consumers to filter news that complements their prior convictions.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of information to influence decision‐making has gained increasing attention in the literature. Consequently, information provision experiments—economic experiments in which information is provided and/or varied to investigate the choice of economic agents (Haaland et al, 2022) have increased over the last decade. For instance, Haaland et al (2022) showed that the number of information provision experiments published in top economics journals in 2020 is more than five times the number published in the same outlets in 2010, suggesting the growing importance of these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It helps economic agents to mitigate uncertainty (Handel & Schwartzstein, 2018) and is critical in their preference formation (Bateman et al, 2009). Information also affects beliefs and perceived constraints, which are essential in decision‐making (Haaland et al, 2022). These functions of information explain the growing attention to information's effects on preferences and welfare estimates.…”
Section: Introductionmentioning
confidence: 99%